ISRÂILIYYÂT DALAM TAFSIR AL-QUR’ÂN ALAZHÎM KARYA IBNU KATSIR - Supriyanto Supriyanto (UIN Raden Mas Said Surakarta, 2015)
This article ecxplores about isrâiliyyât in Tafsîr al-Qur'ân al-Adzim Ibn Kathir. According to the assessment of the scholarsnarrations contained in this book belong to the most valid.Nevertheless, it still raises a dilemma in this book, when the discoveryof some the history that is included in isrâiliyyât. Isrâiliyyât story isentered in round (without any selection) into a book of commentary,will be able to damage the face and purity of the interpretation of thetafsir Koran. This is, because the stories contain superstition andfalsehood that develops in the middle of the Jews and Christians, thenthey develop and distribute to the Muslims. In this book, there are atleast three categories isrâiliyyât, namely: first, history isrâiliyyât whichhe put but also criticized and commented upon truth, second, storyisrâiliyyât he put but without justified and also blamed, and the third,the story isrâiliyyât the inclusion in round without comment fromhim.